Pengendalian Penyakit Layu Pisang dengan Fusarium Nonpatogenik dan Fluorescent pseudomonads - Christanti Sumardiyono; Arif Wibowo; Suryanti Suryanti (Jurnal Perlindungan Tanaman Indonesia, 2007)
The study was aimed to know the ability of fluorescent pseudomonads and nonpathogenic Fusarium for controlling fusarium wilt of banan. The research was conducted both in the laboratory and glass ouse in the Faculty of Agriculture Gadjah Mada University. Laboratorial trial incuded the examining of antagonistic capacity in vitro and the population of these two antagonistic microorganism in compost medium. The examination of the effect of these two microorganisms in compost medium against fusarium wilt of banana Ambon Kuning cultivar was conducted in a glass house. The result showed that there was no antagonistic mechanism occured between fluorescent pseudomonads and nonpathogenic Fusarium. The treatment of compost with fluorescent pseudomonads or/and nonpathogenic Fusarium showed that there were differences on the optimum population of these two antagonistic microorganisms. Fluorescent pseudomonads attained its optimum population one week after inoculation while nonpathogenic Fusarium attained its optimum population two weeks after inoculation. The glass house trial showed taht compost enriched with two microorganisms with one week inocubation time reduced percentage of wilted leaves, although it was nonsignificant with control treatment. Field experiment should be conducted with higher population density of antagonist microorganisms.